2005
DOI: 10.1242/jeb.01531
|View full text |Cite
|
Sign up to set email alerts
|

Androgen control of immunocompetence in the male house finch,Carpodacus mexicanusMüller

Abstract: SUMMARY The immunocompetence handicap (ICH) hypothesis predicts that elevated levels of the gonadal androgen testosterone (T) entail obligatory costs, such as immunosuppression, but evidence supporting this immunosuppressive influence is equivocal. To investigate this question, adult males house finches, Carpodacus mexicanus, were exposed to short days and chronically treated with T-filled (T males; N=10) or empty (C males; N=10) Silastic capsules. Testosterone administration increased plasma T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 69 publications
(96 reference statements)
1
30
0
2
Order By: Relevance
“…In contrast to testicular size, cloacal protuberance growth in finches was not affected by food availability. Cloacal protuberance size usually varies in parallel with testis size (Perfito et al, 2005;Small et al, 2008) and both are influenced by circulating testosterone levels (Deviche and Cortez, 2005). Although food-restricted finches had lower plasma testosterone than ad libitum-fed finches, it appears that the precise relationship between plasma testosterone and cloacal protuberance growth is somewhat dissociated, an observation that is not without precedent (Wingfield et al, 2012).…”
Section: Testicular Response To Energetic Deficitmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to testicular size, cloacal protuberance growth in finches was not affected by food availability. Cloacal protuberance size usually varies in parallel with testis size (Perfito et al, 2005;Small et al, 2008) and both are influenced by circulating testosterone levels (Deviche and Cortez, 2005). Although food-restricted finches had lower plasma testosterone than ad libitum-fed finches, it appears that the precise relationship between plasma testosterone and cloacal protuberance growth is somewhat dissociated, an observation that is not without precedent (Wingfield et al, 2012).…”
Section: Testicular Response To Energetic Deficitmentioning
confidence: 99%
“…A validated (Deviche and Cortez, 2005) commercial enzyme-linked immunoassay (Enzo Life Sciences, Farmingdale, NY, USA) was used to measure plasma testosterone. Instructions outlined by the manufacturer were followed.…”
Section: Plasma Testosterone and Cort Assays Testosteronementioning
confidence: 99%
“…In addition, SMRs of every male B. gauderio we tested exceeded those of every female, despite the presumed trade-off (Fig.6). Androgens increase signal power in B. gauderio (Allee et al, 2009), and also reduce immunocompetence in a variety of vertebrates (Cutolo et al, 2002;Deviche and Cortez, 2005). Thus, males with the strongest signals could be obtaining the energy needed to boost signal power by reallocating energy away from immune function or other 'discretionary' functions (Wedekind and Folstad, 1994).…”
Section: The Gymnotiform Case Study -Comparing Signal Costs By Sexmentioning
confidence: 99%
“…There is good evidence of the immunosuppressive nature of T in laboratory mammals (Grossman, 1985), and several manipulative avian studies have found a deleterious effect of elevated T on humoral immunity (Duffy et al, 2000;Peters, 2000;Casto et al, 2001;Buchanan et al, 2003;Owen-Ashley et al, 2004;Deviche and Cortez, 2005), as well as on cell-mediated immunity (Duffy et al, 2000;Casto et al, 2001;Owen-Ashley et al, 2004;Deviche and Cortez, 2005;Boughton et al, 2007;Fargallo et al, 2007). However, other studies have found no such effect on either humoral (Hasselquist et al, 1999;Roberts et al, 2007a) or cellmediated immunity (Buchanan et al, 2003;Greenman et al, 2005;Roberts et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%